Viscoelastic Hemostatic Assays in Sepsis: From Pathophysiology to Potential Clinical Implications - Bonetti, Claudia; Silvestri, Ivan; Caccioppola, Alessio; Meli, Andrea; Grasselli, Giacomo; Panigada, Mauro (Seminars in Thrombosis and Hemostasis, 2025)
Sepsis is a complex syndrome characterized by physiological, pathological, and biochemical abnormalities induced by infection, with up to 70% of patients experiencing coagulation alterations, ranging from subclinical coagulopathy to disseminated intravascular coagulation (DIC). The multifactorial nature of sepsis-related coagulopathy and the limitations of standard diagnostic parameters, such as platelet count and traditional coagulation tests, complicate its definition and management. Assessing coagulopathy related to sepsis presents significant challenges due to current definitions primarily focusing on diagnosing advanced stages of coagulation dysfunction, thereby overlooking the dynamic and evolving nature of the condition. Viscoelastic hemostatic assays (VHAs) have emerged as valuable tools in this context, offering real-time insights into clot formation, stabilization, and lysis by integrating both plasma and cellular contributions to coagulation. Data from clinical studies suggest that early stages of sepsis coagulopathy are characterized by hypercoagulability, while advanced stages may lead to hypocoagulability and DIC. Moreover, specific point-of-care assays can evaluate platelet performance in the clotting mechanism and potentially help the diagnosis of platelet dysfunction in sepsis. Additionally, the phenomenon of fibrinolysis inhibition contributes to the persistence of fibrin clots, promoting tissue ischemia and multiorgan dysfunction. Modified VHAs appear promising for detecting fibrinolysis impairment, which is associated with poorer outcomes, but the standardization of results is still a work in progress. Incorporating VHAs data into treatment strategies could lead to more targeted therapies, potentially improving outcomes in septic patients by addressing both hypercoagulable and hypocoagulable states, as well as fibrinolysis abnormalities.
Keywords: viscoelastic; thromboelastography; TEG; coagulation; sepsis; septic shock; coagulopathy